2010
DOI: 10.1103/physrevlett.105.158101
|View full text |Cite
|
Sign up to set email alerts
|

DNA–DNA Interactions in Tight Supercoils Are Described by a Small Effective Charge Density

Abstract: DNA-DNA interactions are important for the assembly of DNA nanostructures and during biological processes such as genome compaction and transcription regulation. In studies of these complex processes, DNA is commonly modeled as a homogeneously charged cylinder and its electrostatic interactions are calculated within the framework of the Poisson-Boltzmann equation. Commonly, a charge adaptation factor is used to address limitations of this theoretical approach. Despite considerable theoretical and experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
153
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 98 publications
(165 citation statements)
references
References 39 publications
11
153
0
1
Order By: Relevance
“…After DNA stretching and initial characterization of the DNA, proteins were added, and changes in DNA length were observed as a function of applied force and DNA turns. Torque values were calculated based on previous theoretical work (24,38) (SI Appendix). In-house-written software used for these calculations is available for download at the Web site of R.S.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After DNA stretching and initial characterization of the DNA, proteins were added, and changes in DNA length were observed as a function of applied force and DNA turns. Torque values were calculated based on previous theoretical work (24,38) (SI Appendix). In-house-written software used for these calculations is available for download at the Web site of R.S.…”
Section: Methodsmentioning
confidence: 99%
“…To clearly distinguish between the two models, we use here single-molecule DNA supercoiling to directly reveal the kinetics and the extent of R-loop formation and dissociation (22)(23)(24). Moreover, our assay provides quantitative insight into the dependence of these processes on DNA supercoiling.…”
mentioning
confidence: 99%
“…The side-by-side interaction between DNA fragments has been studied in some detail previously [50][51][52]. Seidel et al [50] demonstrated that in the presence of monovalent ions, the effective repulsion between DNA supercoils corresponds to 40 % of the DNA charge. Thus, it is important to examine whether ultra-short DNA fragments show electrostatic repulsion sufficient to give rise to considerably anisotropic interaction that would lead to the formation of columns.…”
Section: Resultsmentioning
confidence: 99%
“…Assuming that, in physiological conditions, half of the charges from the phosphate groups are screened by counter ions (42), one can think that each bead (σ = 2.5 nm ' 8 bp) contains a total charge of q b = 16q e =2, where q e is the electron charge. Within this assumption, we can map the external force applied onto each bead to an effective electric field E = f =q b .…”
Section: Methodsmentioning
confidence: 99%